Germany in the European Union: economic policy under ceded sovereignty - Horst Siebert (Kiel Institute for World Economics (IfW), 2004)
The member states of the European Union have given up sovereignty in quite a number of policy areas and subjected themselves to joint decisionmaking at the European level. Policy instruments are no longer available nationally in many policy areas, including monetary policy, trade policy, the more important part of competition policy, subsidy control, and a large number of the regulations in the product market, the environmental arena, and the capital market. The maneuvering space for national economic policy-makers has been reduced considerably. In quite a few areas in which decisions are taken with a qualified majority, the member countries can be outvoted and have to accept the decisions taken by others. This paper surveys the new decision space of economic policy of a member state including the latest constitutional arrangement.
Keywords: E58; F15; H77; 330; European integration; sovereignty; EU constitution; Europäische Integration; Souveränität; Verfassung; Deutschland; EU-Staaten